The Gamma Interferon (IFN-γ)-Inducible GTP-Binding Protein IGTP Is Necessary for Toxoplasma Vacuolar Disruption and Induces Parasite Egression in IFN-γ-Stimulated Astrocytes - Melzer, T. (American Society for Microbiology (ASM), 2008)
Toxoplasma gondii is a common central nervous system infection in individuals with immunocompromised immune systems, such as AIDS patients. Gamma interferon (IFN-γ) is the main cytokine mediating protection against T. gondii. Our previous studies found that IFN-γ significantly inhibits T. gondii in astrocytes via an IFN-γ-inducible GTP-binding protein (IGTP)-dependent mechanism. The IGTP-dependent-, IFN-γ-stimulated inhibition is not understood, but recent studies found that IGTP induces disruption of the parasitophorous vacuole (PV) in macrophages. In the current study, we have further investigated the mechanism of IFN-γ inhibition and the role of IGTP in the vacuolar disruption in murine astrocytes. Vacuolar disruption was found to be dependent upon IGTP, as PV disruption was not observed in IGTP-deficient (IGTP(−/−)) astrocytes and PV disruption could be induced in IGTP(−/−) astrocytes transfected with IGTP. Live-cell imaging studies using green fluorescent protein-IGTP found that IGTP is delivered to the PV via the host cell endoplasmic reticulum (ER) early after invasion and that IGTP condenses into vesicle-like structures on the vacuole just prior to PV disruption, suggesting that IGTP is involved in PV disruption. Intravacuolar movement of the parasite occurred just prior to PV disruption. In some instances, IFN-γ induced parasite egression. Electron microscopy and immunofluorescence studies indicate that the host cell ER fuses with the PV prior to vacuolar disruption. On the basis of these results, we postulate a mechanism by which ER/PV fusion is a crucial event in PV disruption. Fusion of the ER with the PV, releasing calcium into the vacuole, may also be the mechanism by which intravacuolar parasite movement and IFN-γ-induced parasite egression occur.